FAKTOR DETERMINAN KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI DKI JAKARTA - Tri Cahyo Utomo Wirawan; Ari Hadi Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The probability of an auditor found and reported a mistatement or an error due to fraud that occurs in a client's accounting system in perform the task called as audit quality. This study aims to determine the effect of competency, independency, professionalism, audit tenure and audit delay on audit quality. The research object consist of auditors who work in an active Public Accounting Firm (KAP) located in the DKI Jakarta area. The sampling technique used purposive sampling technique, obtained 85 auditor respondents from 12 active Public Accounting Firms listed in the KAP database published by the Ministry of Finance of the Republic of Indonesia in the DKI Jakarta area. The data analysis technique used is descriptive statistical analysis, data quality test, classical assumption test and hypothesis testing using SPSS Statistics 22. The results of the study conclude that there is sufficient evidence that the variables of competency, independency, professionalism and audit tenure have significant positive effect on audit quality. On the other hand, there is not enough evidence that the audit delay variable has a significant negative effect on audit quality. Keywords: Competency, Independency, Professionalism, Audit Tenure, Audit Delay, Audit Quality. References: Ade Nahdiatul Hasanah, M. S. P. (2018). Pengaruh Ukuran Perusahaan, Audit Tenure Terhadap Kualitas Audit. Jurnal Akuntansi, 5(1), 11–21. Retrieved from https://akuntabilitasuinjkt.wordpress.com/tag/audit-tenure/ Agoes, S. (2018). Auditing (Edisi 5; E. S. Suharsi, Ed.). Jakarta Selatan: Salemba Empat. Arens, A. A., Elder, R. J., & Beasley, M. S. (2017). Auditing and Assurance Services (Edisi 16). London: Pearson Education. Ashton, R. H., Willingham, J. J., & Elliott, R. K. (1987). An empirical analysis of audit delay. Journal of Accounting Research, 275–292. Bustami, A. (2013). Pengaruh Independensi, Akuntabilitas Dan Profesionalisme Auditor Terhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik di DKI Jakarta). 66(2012), 1–168. CNN. (2019). Kemenkeu Beberkan Tiga Kelalaian Auditor Garuda Indonesia. Retrieved November20, 2020, from CNN Indonesia website https://www.cnnindonesia.com/ekonomi/20190628124946-92-407304/kemenkeu-beberkan-tiga- kelalaian-auditor-garuda-indonesia Committee, A. F. A. S. (2000). SEC Auditor Independence Requirements. AAA Financial Accounting Standards Committee. Accounting Horizons, 15(4), 373–386. Cooper, D. R., & Schindler, P. S. (2017). Metode Penelitian Bisnis, Edisi 12. Jakarta: Salemba Empat. DeAngelo, L. E. (1981). Auditor size and Audit Quality. Journal of Accounting and Economics, 3(3), 183–199. Duff, A. (2004). Dimensions of Audit Quality (First; A. Rowe, Ed.). Great Britian: The Institute of Chartered Accountants of Scotland CA. futri, S., & Juliarsa, G. (2014). Pengaruh Independensi, Profesionalisme, Tingkat Pendidikan, Etika Profesi, Pengalaman, Dan Kepuasan Kerja Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik Di Bali. E-Jurnal Akuntansi, 8(1), 41–58. Ghozali, I. (2016). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 23 (Edisi 8). Semarang: Universitas Diponegoro. Gunawan, L. D. (2012). Pengaruh Tingkat Independensi, Kompetensi, Obyektifitas, dan Integritas Auditor terhadap Kualitas Audit yang Dihasilkan Kantor Akuntan Publik di Surabaya. Jurnal Ilmiah Mahasiswa Akuntansi, 1(4), 44–48. Retrieved from http://journal.wima.ac.id/index.php/JIMA/article/view/245%5Cnhttp://jurnal.wima.ac.id/index.p hp/JIMA/article/view/245 Hall, R. H. (1968). Professionalization and bureaucratization. American Sociological Review, 92–104. Herianti, E., & Suryani, A. (2016). Pengaruh Kualitas Auditor , Audit Delay dan Audit Tenure Terhadap Kualitas Audit Perbankan yang Terdaftar di BEI Periode 2012-2014. Prosiding Seminar Nasional INDOCOMPAC, 416–425. Herry. (2017). Auditing Dan Asurans (Adipramono, Ed.). Jakarta: PT Grasindo. IAI. (2011). SA Seksi 220. Standar Auditing, (01), 1–3. Idris, M. (2011). Pengaruh Profesionalisme, Karakteristik Personal Auditor Dan Batasan Waktu Audit Terhadap Kualitas Audit. E-Jurnal Akuntansi, 1–131. Jensen, M. C., & Meckling, W. H. (1976). Theory Of The Firm: Managerial Behavior, Agency Costs And Ownership Structure. Journal of Financial Economics, 3(10), 305–360. Kurniawan, S. L. (2019). Pengaruh Independensi, Pengalaman Audit, Etika Auditor, Komitmen Auditor dan Time Budget Pressure Terhadap Kualitas Audit (KAP Solo dan Yogyakarta ). 1–20. Messier, W. F., Glover, S. M., & Prawitt, D. F. (2017). Auditing & Assurance Services. New York: McGraw Hill Education. Pertiwi, N., & Agusti, R. (2013). Pengaruh Kompetensi, Independensi, Profesionalisme Terhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik Se Sumatera). TEKUN: Jurnal Telaah Akuntansi Dan Bisnis, 8(1), 1–13. Prabhawanti, P. P., & Widhiyani, N. L. S. (2018). Pengaruh Besaran Fee Audit dan Independensi Terhadap Kualitas Audit dan Etika Profesi Auditor Sebagai Moderasi. E-Jurnal Akuntansi,24, 2247. Pratiwi, A. A. C., Suryandari, N. N. A., & Susandya, A. P. G. B. A. (2020). Pengaruh Profesionalisme, Independensi dan Kompetensi Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik Di Provinsi Bali. Jurnal Kharisma, 21(1), 1–9. Santhi, L. G. M. ., & Ratnadi, N. M. D. (2013). Independensi Auditor Sebagai Pemediasi Pengaruh Audit Fee Dan Time Budget Pressure Pada Kualitas Audit. Journal of Chemical Information and Modeling, 01(01), 1689–1699. Sarwoko, I. (2014). Pengaruh Ukuran Kap Dan Masa Perikatan Audit Terhadap Penerapan Prosedur Audit Untuk Mendeteksi Risiko Kecurangan Dalam Laporan Keuangan, Serta Implikasinya Terhadap Kualitas Audit. Jurnal Akuntansi, XVIII(01), 1–20. Sisna Armawan, I. P., & Wiratmaja, I. D. N. (2020). Pengaruh Pengalaman, Kompetensi, Independensi dan Fee Audit pada Kualitas Audit. E-Jurnal Akuntansi, 30(5), 1208. Sugiyono. (2017). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Sutani, D. (2017). Pengaruh Fee Audit, Audit Tenure, Audit Delay dan Komite Audit Terhadap Kualitas Audit (Studi Empiris pada Perusahaan Transportasi, Infrastruktur dan Ultilities yang terdaftar di Bursa Efek Indonesia Tahun 2014-2017). Al-Buhuts, 13(2), 127–145. Tandiontong, M. (2016). Kualitas Audit dan Pengukurannya. Bandung: Alfabeta. Teijlingen, E. R. Van, & Hundley, V. (2001). The Importance of Pilot Studies. Social Research Update, 2001(35), 4694–4699. Tjun, T. L., Marpaung, E. I., & Setiawan, S. (2012). Pengaruh Kompetensi dan Independensi AuditorTerhadap Kualitas Audit. Jurnal Akuntansi, 4(1), 33–56. Wardhani, A. A. I. T. W. (2018). Pengaruh Kompetensi, Akuntabilitas dan Independensi pada Kualitas Audit dengan Etika Auditor Sebagai Variabel Moderasi. E-Jurnal Akuntansi Universitas Udayana, 23(4), 1–29. Werastuti, D. N. S. (2013). Pengaruh Auditor Client Tenure, Debt Default, Reputasi Auditor, Ukuran Klien dan Kondisi Keuangan Terhadap Kualitas Audit Melalui Opini Audit Going Concern. VOKASI Jurnal Riset Akuntansi, 2(1), 99–116. Wiratama, W. J., & Budiartha, K. (2015). Pengaruh Independensi, Pengalaman Kerja, Due Professional Care dan Akuntabilitas Terhadap Kualitas Audit. E-Jurnal Akuntansi, 91–106